Riwayat Penyakit Menjadi Salah Satu Faktor Penyebab Stunting pada Anak Usia 1-5 Tahun - Vicky Afni Qomariyah; Siti Fatmawati (Pusat Riset dan Inovasi Nasional, 2024)
The stunting rate for toddlers in Surakarta increased from 2.0% (2021) to 2.7% (2022). The Pajang Community Health Center has the highest number of stunted toddlers, namely 142 toddlers. A history of infectious disease increases the risk of stunting 3-8 times. Objective: To describe the history of stunting in toddlers in the Pajang Community Health Center working area. Method: This research is quantitative descriptive. The research population was 187 stunted toddlers. The sampling technique used total sampling with inclusion and exclusion criteria, so that 142 respondents were obtained. Results: Characteristics of toddlers: 1-3 years old (69.7%), male (48.6%), and exclusively breastfed (81.7%). Characteristics of mothers of toddlers: aged 20-34 years (74.6%), not working (78.9%), and high school education (50.7%). History of infectious diseases in children under five: diarrhea (42.3%). Non-communicable diseases liver disorders (1.4%) and anemia (1.4%). The genetic disease is Congenital Heart Disease (0.7%). A total of 40 toddlers (28.2%) had no history of disease. Conclusion: Stunted toddlers are predominantly 1-3 years old, male, and exclusively breastfed. Mothers of toddlers aged 20-34 years, not working, and have a high school education. The dominant infectious diseases are diarrhea, non-communicable diseases anemia and liver disorders, as well as the genetic disease CHD. Toddlers with no history of illness in small numbers.